Perancangan Alat Destilasi Limbah Ampas Tahu Menjadi Bahan Bakar Bioethanol Melalui Metode Quality Function Deployment (QFD) - Arifianto, Deni; Suwondo, Ampar Jaya; Abdullah, M. Hasan; Octavia, Chendrasari Wahyu; Hindratmo, Astria; Purnamayudhia, Onny (Journal of System Engineering and Technological Innovation, 2023)
Fuel oil is experiencing an increase in demand in various sectors of life impacting the distribution process and meeting market needs. Bioethanol is a new and renewable energy with great potential to replace fuel oil. One alternative material for producing bioethanol is tofu dregs. Tofu dregs raw material processing can be done by distillation process. This study uses conventional distillation with the addition of components which are expected to produce bioethanol with good quality. The design of the distillation apparatus uses the QFD (Quality Function Development) approach. So the purpose of this study was to determine the technical characteristics of the bioethanol distillation system based on customer needs. The design of a bioethanol distillation apparatus made from Tofu Dregs using the QFD method resulted in several criteria for the device expected by the customer, including fast distillation time, amount of ethanol production, fermentation time, ergonomics, hydrolysis time, octane content and solution composition. The importance level of fast distillation time was 4.06, total ethanol production was 3.8, fermentation time was 3.67, ergonomic design was 3.63, hydrolysis time was 3.26, octane level was 3.21 and solution composition was 3.15. The resulting tool is capable of processing tofu dregs into bioethanol. The dimensions of the tool are 1264 mm in length, 1226 mm in width, and a total tool height of 1275 mm. The distillation apparatus is equipped with a set of vessels, condensers, coolers and heaters.